Knowledge management in electronic government : an exploratory study of local authorities in Malaysia / Kalsom Salleh and Syed Noh Syed Ahmad - Salleh, Kalsom; Syed Ahmad, Syed Noh (Institute of Research, Development and Commercialization (IRDC), 2006)
Public sector organizations in developing countries have not received much attention in the research literature of Knowledge Management (KM). The potential impact of KM in the public sector organizations affecting the stakeholders is greater compared to private sector organizations. This paper explores the role of KM in Local Authorities in the broader perspective towards achieving the Electronic Government (E-Government) orientation in Malaysia. This research used a survey questionnaire distributed to all senior and middle management government officers in a multiple case study of three types of Local Authorities located in the Kuala Lumpur Federal Territory and the state of Selangor. These officers are responsible for strategic policies and operational management in various departments of the Local Authorities. The responses from the questionnaires will provide answers to two critical areas: awareness and readiness of KM adoption in terms of physical assets (KM technology) and intellectual assets (ICT skills and ICT trainings provided to management staff) and also the perceived opportunities and challenges in using KM as a strategic tool in developing knowledge - based civil service and the implementation of E-Government.